Hydrolysis of Hemicellulose and Derivatives—A Review of Recent Advances in the Production of Furfural - Delbecq, Frederic; Wang, Yantao; Muralidhara, Anitha; El Ouardi, Karim; Marlair, Guy; Len, Christophe (Frontiers in Chemistry, 2018)
Biobased production of furfural has been known for decades. Nevertheless, bioeconomy and circular economy concepts is much more recent and has motivated a regain of interest of dedicated research to improve production modes and expand potential uses. Accordingly, this review paper aims essentially at outlining recent breakthroughs obtained in the field of furfural production from sugars and polysaccharides feedstocks. The review discusses advances obtained in major production pathways recently explored splitting in the following categories: (i) non-catalytic routes like use of critical solvents or hot water pretreatment, (ii) use of various homogeneous catalysts like mineral or organic acids, metal salts or ionic liquids, (iii) feedstock dehydration making use of various solid acid catalysts; (iv) feedstock dehydration making use of supported catalysts, (v) other heterogeneous catalytic routes. The paper also briefly overviews current understanding of furfural chemical synthesis and its underpinning mechanism as well as safety issues pertaining to the substance. Eventually, some remaining research topics are put in perspective for further optimization of biobased furfural production.